Band parameters for self-broadened ammonia gas in the range 0.74 to 5.24 mu m to support measurements of the atmosphere of the planet Jupiter - Bowles, N; Calcutt, S; Irwin, P; Temple, J (2008)
We present new measurements and modelling of low-resolution transmission spectra of self-broadened ammonia gas, one of the most important absorbers found in the near-infrared spectrum of the planet Jupiter. These new spectral measurements were specifically designed to support measurements of Jupiter's atmosphere made by the Near-Infrared Mapping Spectrometer (NIMS) which was part of the Galileo mission that orbited Jupiter from 1995 to September 2003. To reach approximate jovian conditions in the lab, a new gas spectroscopy facility was developed and used to measure self-broadened ammonia spectra from 0.74 to 5.2 μm, virtually the complete range of the NIMS instrument, for the first time. Spectra were recorded at temperatures varying from 300 to 215 K, pressures from 1000 to 33 mb and using three different path lengths (10.164, 6.164 and 2.164 m). The spectra were then modelled using a series of increasingly complex physically based transmittance functions. © 2008 Elsevier Inc. All rights reserved.